Inspiration and Institution in 1960s Anglican Radicalism: The Cases of Nick Stacey and John Robinson - Brewitt-Taylor, Sam (Studies in church history, 2021)
This article explores how Nick Stacey and John Robinson, two central figures in Anglican radicalism, navigated the tensions between their institutional embeddedness and their radical theological inspiration during the ‘religious crisis’ of the 1960s. These tensions operated on the level of strategy, as radicals calculated the opportunities and costs of leaving Anglican institutions, but also on the level of emotion, as radicals weighed institutional loyalties that went deep inside themselves. In the mid-1960s, Anglican radicals attempted to resolve these tensions by campaigning to transform the Church of England. By the early 1970s, however, the failure of these attempts had led to the movement's disintegration, leaving individuals to address the emotional tensions between inspiration and institution in their own particular ways. Thus Anglican radicals failed to evade the central paradox of their movement, namely that their brief moment of prominence in the early 1960s owed much to the prestige of the institution they were critiquing so influentially.